UNDERSTANDING BRAND LOYALTY IN INDONESIAN SKINCARE THROUGH ENGAGEMENT, EXPERIENCE, AND BRAND IMAGE - Dini Elida Putri; Fenisi Resty; Endang Purbaningsih (UPT Publikasi Ilmiah UNISBA, 2026)
Emerging skincare market, bringing fierce competition between skincare brands, including Indonesian skincare or local brands. How brand engagement, experience, and brand image valued by consumers will define business future. The purpose of this study is to examine and analyze the influence of customer brand engagement, brand experience and brand image on brand loyalty of female consumers towards Indonesian Skincare products,and conducted in Sungai rumbai District. The research method is quantitative method, with valid and reliable questionairres distributed to research sample of 379 respondents. Data calculated using SPSS with validity test, reliability test, descriptive analysis, correlation analysis, multiple linear analysis, classical assumption test, t-test, F-test and coefficient of determination (R2). The results of hypothesis testing reveals that all independent variables consisting of brand engagement, brand experience, brand image has partially and simultaneously positive and significant effect on the dependent variable, brand loyalty. As well as producing a coefficient of determination of R2= 0.463 (46.3%). This means that the influence of all independent variable on dependent variable is 46.3% and the remaining 53.7% influenced by other variables. Thus, engagement, experience and image of Indonesian skincare brand pays significant part in influencing brand loyalty toward local skincare products, must be manage continuously.